METODOLOGI PEMBELAJARAN ANAK USIA DINI (PAUD) - Mahmudi Mahmudi; Kandiri Kandiri (LP2M Universitas Ibrahimy, 2018)
In the implementation of teaching and learning activities, the teacher needs to know the teaching components such as teaching methods because without using methods, teaching and learning activities do not work as expected. Teaching methods as a path to provide opportunities for students in many kinds of lessons, because those are the efforts of the teacher in guiding, directing, or organizing learning in a series of activities that the students learn to accept, understand, respond, possess, master and develop it. Teaching methods are one effective and efficient way that teachers use to convey that subject matter, as well as coaching, direction, learning organizers so that children can experience all kinds of subjects. While there are factors that influence the number of teaching methods are as follows: a) Objectives of various types and functions. b) Students who have varying degrees of maturity, c) Situations of various conditions, d) Facilities that different in quality and quantity, e) Teachers’ personality that different in professional abilities.